2018
DOI: 10.3389/fpsyt.2018.00008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Associated with Brain Volume Reduction in Systemic Lupus Erythematosus Patients without Major Neuropsychiatric Manifestations

Abstract: The aim of the study was to find structural brain changes in systemic lupus erythematosus patients without major neuropsychiatric manifestations [non-neuropsychiatric systemic lupus erythematosus (non-NPSLE)] using quantitative magnetic resonance imaging (MRI) and possible associations with clinical characteristics. 89 non-NPSLE patients with normal conventional MRI and 84 healthy controls (HCs) were recruited. The whole brain gray matter volume (GMV) and white matter volume (WMV) were calculated for each indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
5
14
0
Order By: Relevance
“…Additionally, we found that HCQ might prevent HIPV reduction. This is consistent with our previous studies which showed that ISA had protective effects on brain atrophy in SLE patients (7,8,21). In our studies, ISA included CTX and HCQ.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, we found that HCQ might prevent HIPV reduction. This is consistent with our previous studies which showed that ISA had protective effects on brain atrophy in SLE patients (7,8,21). In our studies, ISA included CTX and HCQ.…”
Section: Discussionsupporting
confidence: 93%
“…Bilateral HIPV of female patients were significantly less than those of male patients. It was consistent with another study of our team, in which we found that female SLE patients had significantly lower whole brain grey matter volume (GMV) and WMV than male patients (21). We hypothesized that these findings might be related to the higher estrogen levels in females.…”
Section: Discussionsupporting
confidence: 91%
“…One caveat of our study is that we did not include neuropsychiatric SLE 7 patients for this evaluation, and did not perform functional magnetic brain resonance imaging or cerebrospinal fluid auto-antibody detection. 3 , 26 Nevertheless, we found a positive correlation between disease duration and the affected domains as evaluated by implementing the gold standard.…”
Section: Discussionmentioning
confidence: 68%
“…OPCs establish physical contacts with functionally relevant neuronal domains and form in parallel with neuronal synaptogenesis, including dendrites, somata, nodes of Ranvier and synaptic cleft [ 110 – 112 ]. It has been shown that elevated glutamate levels and gene expression of glutamate receptors are found in the plasma, cerebrospinal fluid (CSF) and locus coeruleus of postmortem brains from patients with depression [ 113 ]. Although the pathological mechanism is unclear, researchers found that MDD patients treated with the antidepressant venlafaxine demonstrated decreased glutamate levels in CSF, indicating a correlation between the attenuation or dysfunction of the glutamatergic system and antidepressant treatment of MDD [ 114 ].…”
Section: Neurotransmitters and Their Receptors In Depressionmentioning
confidence: 99%